The Right to Education for Children with Special Needs: A Juridical Review of Implementation Challenges and the Fulfillment of Educational Rights in Indonesia - Liana Setiawati; Elina Adi Wijayanti (Jurnal Sosial Sains dan Komunikasi, 2026)
Education is a fundamental human right that must be guaranteed equally to all children, including children with special needs (CSNs). Indonesia has established a comprehensive legal framework to protect the educational rights of CSNs through constitutional provisions, child protection legislation, disability laws, and policies promoting inclusive education. However, the implementation of these legal guarantees remains inconsistent due to disparities in accessibility, inadequate educational infrastructure, shortages of qualified teachers, social stigma, and unequal funding across regions. This study aims to analyze the juridical basis of the educational rights of children with special needs, examine the challenges in implementing inclusive education, and identify strategies to strengthen the fulfillment of these rights in Indonesia. The study employed a normative juridical approach using a literature review method. Data were collected from primary and secondary legal sources, including statutory regulations, government policies, scholarly books, and scientific journal articles, and were analyzed using qualitative descriptive analysis. The findings indicate that although Indonesia possesses a strong legal foundation supporting inclusive education, its implementation has not yet been fully effective. Major challenges include limited accessibility, inadequate disability-friendly facilities, insufficient numbers of Special Assistant Teachers, uneven policy implementation, and regional disparities in educational services. Strengthening policy implementation, increasing teacher recruitment and competency, improving cross-sector collaboration, and ensuring equitable funding allocation are essential to achieving inclusive, equitable, and high-quality education for children with special needs.